High Metabolic Function and Resilience of NKG2A-Educated NK Cells - Highton, Andrew J.; Diercks, Björn-Philipp; Möckl, Franziska; Martrus, Gloria; Sauter, Jürgen; Schmidt, Alexander H.; Bunders, Madeleine J.; Körner, Christian; Guse, Andreas H.; Altfeld, Marcus (Frontiers in Immunology, 2020)
Natural killer (NK) cells are an important component of the innate immune system for the control of intracellular pathogens and cancer cells. NK cells demonstrate heterogeneous expression of inhibitory surface receptors. Signalling through these various receptors during NK cell development promotes functionality, referred to as NK cell education. Here we investigated the impact of education on NK cell metabolism by functional assessment of critical metabolic pathways and calcium signalling. Educated NK cells had an increased uptake of the metabolic substrates 2-NBDG, a fluorescent glucose analogue, and BODIPY FL C16, a fluorescent palmitate, compared to uneducated NK cells. Comparison of NK cells educated via KIR or NKG2A showed that NKG2A-educated NK cells were the main contributor to these differences in uptake of metabolites, and that NKG2A-educated NK cells were functionally more resilient in response to metabolic blockade of oxidative phosphorylation. Furthermore, NKG2A-educated NK cells exhibited higher peak calcium concentration following stimulation, indicating stronger signalling events taking place in these educated NK cells. These results demonstrate that cellular metabolism plays an important role in the functional differences observed between educated and uneducated NK cells, and show that NKG2A-educated NK cells remain more functionally competent than KIR-educated NK cells when oxidative phosphorylation is restricted. Understanding metabolic programming during NK cell education may unveil future targets to manipulate NK cell function for use in clinical settings, such as cancer therapies.